2021
DOI: 10.1590/s1678-3921.pab2021.v56.02046
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of cowpea genotypes in southwestern Brazilian Amazon

Abstract: The objective of this work was to evaluate the agronomic performance of cowpea (Vigna unguiculata) genotypes over three crop years, in the ecosystem of Rio Branco, in the state of Acre, Brazil. The experiments were carried out in the 2016, 2017, and 2018 crop seasons, in a randomized complete block design, with four replicates. Eight agronomic traits were evaluated in 14 cowpea genotypes, which included: 12 lines (BDO 1-5-11, BDO 1-5-15, BDO 1-5-19, BDO 1-5-24, PDO 1-5-26, PDO 1-5-4, PDO 1-5-5, PDO 1-5-7, PDO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
2
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 10 publications
1
4
2
5
Order By: Relevance
“…This result confirms the extra-large grain size of the cultivar BRS-Imponente (ROCHA; DAMASCENO-SILVA; MENEZES-JÚNIOR, 2017). However, Marinho et al (2021) found grain sizes ranging from 31.50 to 35.50 g 100 grains -1 for the cultivar BRS-Imponente, smaller than the means found in the present study.…”
Section: Grouping Of Meanscontrasting
confidence: 98%
See 4 more Smart Citations
“…This result confirms the extra-large grain size of the cultivar BRS-Imponente (ROCHA; DAMASCENO-SILVA; MENEZES-JÚNIOR, 2017). However, Marinho et al (2021) found grain sizes ranging from 31.50 to 35.50 g 100 grains -1 for the cultivar BRS-Imponente, smaller than the means found in the present study.…”
Section: Grouping Of Meanscontrasting
confidence: 98%
“…The comparison between the overall mean grain size of cultivars of the white class and the overall mean of cultivars of the colors + black class showed superiority for the white class, which differed from the colors + black classes and the overall mean of the cultivars. This result confirms those of the Freire Filho (2011), who reported occurrence of larger grain sizes for cultivars of the white class; in addition, Marinho et al (2021) reported larger grain sizes and rough texture for the cultivars BR-3-Tracuateua and BRS-Imponente. The market demand for cowpea cultivars with larger grains is high in Brazil; thus, cultivars with larger grains have higher prices.…”
Section: Grouping Of Meanssupporting
confidence: 91%
See 3 more Smart Citations